Serum uric acid predictive value and prognostic impact in rheumatoid arthritis’ associated interstitial lung disease - Hu, Qiongwen; Cheng, Xiaocheng; Lan, Ying; Lei, Huxin; Niu, Changchun; Luo, Yang (Frontiers in Medicine, 2025)
ImportanceIt is critical to identify novel biomarkers for the prediction and prognosis of rheumatoid arthritis-associated interstitial lung disease (RA-ILD).ObjectiveThe objective of the study was to investigate the predictive and prognostic significance of serum uric acid (UA) in RA-ILD.Design, setting, and participantsIn this multicenter retrospective cohort study, demographic data, medical history, and laboratory results of 829 RA patients were extracted from electronic medical records between December 2018 and January 2024. The cohort was divided into an RA-ILD group (n = 351) and an RA-no-ILD group (n = 478).Main outcomes and measuresThe primary endpoint was the predictive capacity of baseline UA levels for the occurrence of ILD in RA patients. The secondary endpoints were all-cause mortality and the rehospitalization rate in RA-ILD patients.ResultsThe univariate analysis identified elevated levels of UA as a significant risk factor for the development of ILD in RA patients (OR [95% CI]: 1.68 [1.23–2.28], p = 0.001). The multivariate analysis confirmed that elevated levels of UA remained an independent risk factor. The subgroup analysis demonstrated a stronger predictive utility of elevated UA levels in younger RA patients (age < 65), particularly those with shorter disease duration and no comorbidities (OR [95% CI]: 3.66 [1.66–8.05], p = 0.001; AUCROC = 0.718). During follow-up, RA-ILD patients with elevated UA levels exhibited significantly higher all-cause mortality (22.1% vs. 13.1%; HR [95% CI]: 1.80 [1.03–3.17], p = 0.040) and rehospitalization rates (51.9% vs. 44.4%; HR [95% CI]: 1.41 [1.00–1.98], p = 0.047) compared to those with lower UA levels.Conclusion and relevanceElevated levels of serum UA may serve as a predictive marker for ILD development in RA patients, particularly in younger individuals without comorbidities, and a prognostic indicator for increased mortality and rehospitalization rates in RA-ILD patients.Clinical trial registrationClinicalTrials.gov, identifier NCT06036537.